2019
DOI: 10.1039/c9ra07570d
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide-dT: a polymerisable nucleoside for DNA incorporation

Abstract: Nucleoside derivative Acrylamide-dT can be readily synthesised and incorporated multiple times into DNA sequences at any position via automated synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This multiple-linker strategy has also been employed by Allabush who used it to incorporate an aptamer into a gel for protein electrophoresis. [21] Incorporation of an aptamer into a hybrid system in this manner also has shown to increase stability, [22] and counter any thermal or enzymatic (nuclease) degradation that is often seen with aptamers on their own. [23,24] The aim of this study is to further explore the development of hybrid-MIP nanoparticles (aptaMIP NP) for a protein target (trypsin).…”
Section: Introductionmentioning
confidence: 99%
“…This multiple-linker strategy has also been employed by Allabush who used it to incorporate an aptamer into a gel for protein electrophoresis. [21] Incorporation of an aptamer into a hybrid system in this manner also has shown to increase stability, [22] and counter any thermal or enzymatic (nuclease) degradation that is often seen with aptamers on their own. [23,24] The aim of this study is to further explore the development of hybrid-MIP nanoparticles (aptaMIP NP) for a protein target (trypsin).…”
Section: Introductionmentioning
confidence: 99%
“…Partially following the synthesis of Allabush et al [36], 5-Iodo-2'-deoxyuridine (1.00 g, 2.82 mmol) and palladium acetate (60 mg, 0.28 mmol) were dissolved in DMF (3 mL) in a 10 mL microwave vial, equipped with a small magnetic stirrer bar. Tributylamine (0.67 mL, 2.82 mmol) and N,N'methylenebisacrylamide (1.09 g, 7.06 mmol), were then added.…”
Section: Synthesis Of Acrylamide-dtmentioning
confidence: 99%
“…Partially following the method of Allabush et al the synthesis of the target Acrylamide-dT involved using the commercially available 5-iodo-2'deoxyuridine and substituting the iodine at C5 with an acrylamide group via the Heck reaction with N,N'-methylenebisacrylamide (Figure 1) [36]. A microwave-assisted procedure was used, which was adapted from Fujimoto and allowed the two entities to be coupled together to form Acrylamide-dT in a good yield (75%) [37].…”
Section: Synthesis Of Acrylamide-dtmentioning
confidence: 99%
“…In an in vitro test, Allabush et al found that the acryl­amide group can react with a DNA sequence (5′-GGTTG­GTGTG­GTTGG-3′) to form adducts with bases in different positions, including 5′ end and 7, 9 positions. Adduct formation increased the thermal melting ( T m ) of the DNA sequence from 62.7 °C for unmodified DNA to 66.7 °C for three incorporated acrylamide-dT’s …”
Section: Acrylamidementioning
confidence: 99%
“…Adduct formation increased the thermal melting (T m ) of the DNA sequence from 62.7 °C for unmodified DNA to 66.7 °C for three incorporated acrylamide-dT's. 25 Glycidamide is more reactive than acrylamide according to an in vivo study. Glycidamide−DNA adducts were detected in lung, liver, spleen, and bone marrow tissues of B6C3F1/Tk mice intraperitoneally administered with 0.70 mmol/kg bw/ day acrylamide or glycidamide for 16 days.…”
Section: ■ Acrylamidementioning
confidence: 99%